Prevention of Early-onset Neonatal Group B Streptococcal Disease - Marió, M. J. Soto (MedReviews, LLC, 2013)
Streptococcus agalactiae, also known as Group B Streptococcus (GBS), is an opportunistic pathogen that colonizes the gastrointestinal and genitourinary tracts of up to 50% of healthy adults and newborns; it is responsible for significant morbidity and mortality. Early detection can be used to establish the use of antibiotic prophylaxis to significantly reduce neonatal sepsis. This article reviews methods of detection and prevention of GBS infection in the neonate.